2016
DOI: 10.1016/j.jid.2016.05.094
|View full text |Cite
|
Sign up to set email alerts
|

Nonoverlapping Clinical and Mutational Patterns in Melanomas from the Female Genital Tract and Atypical Genital Nevi

Abstract: Genital melanomas (GM) are the second most common cancer of the female external genitalia and may be confused with atypical genital nevi (AGN), which exhibit atypical histological features but have benign behavior. In this study, we compared the clinical, histologic and molecular features of 19 GM and 25 AGN. We described chromosomal copy number aberrations, and the mutational status of 50 oncogenes and tumor suppressor genes in both groups. Our study revealed that a pigmented lesion occurring in mucosal tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…We documented three novel TP53 mutations (V203L, V274P and P278R) not previously reported in vulvar melanomas . Although several studies of cutaneous melanomas reported an association between Ki‐67 proliferation index and p53 expression with clinical outcome, we did not observe these associations .…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…We documented three novel TP53 mutations (V203L, V274P and P278R) not previously reported in vulvar melanomas . Although several studies of cutaneous melanomas reported an association between Ki‐67 proliferation index and p53 expression with clinical outcome, we did not observe these associations .…”
Section: Discussioncontrasting
confidence: 86%
“…KIT L576P was the most frequently detected variant in our series and is an actionable therapeutic target . KIT Y646D, associated with resistance to imatinib and/or sunitinib, and A829P have not been reported in vulvar melanoma .…”
Section: Discussionmentioning
confidence: 69%
“…We evaluated 50 genes using the Ion Torrent PGM and the Ion Torrent AmpliSeq Cancer Hotspot Panel v2 (Life Technologies, Grand Island, NY). Sequencing methodology was as previously described for genital melanoma and nevi cases (Yelamos et al, 2016).…”
Section: Next Generation Sequencingmentioning
confidence: 99%
“…[30][31][32] Our own group identified KIT mutations in 36.4% of melanomas of the female genital tract. 33 These mutations most commonly occur as missense substitutions in the region encoding the juxtamembrane domain, which are thought to promote constituitive activation of KIT and drive several downstream pathways, including mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase. 32 Additionally, many acral and mucosal melanomas may have focal gains or amplifications of KIT that result in increased kinase activity.…”
Section: Molecularmentioning
confidence: 99%
“…However, up to 15% of patients with vulvar or vaginal melanoma provide a family history of melanoma, and some studies have shown germline mutations in melanocortin type I receptor gene and CDKN2A in these patients. 33,55 Currently, CDKN2A germline mutations are recognized as the most common germline mutation in melanoma. In families with three or more cases of melanoma, CDKN2A germline mutations are thought to predispose to approximately 40% of cases.…”
Section: Inherited and Other Risk Factorsmentioning
confidence: 99%